Perceived Influence of Test Anxiety on the Academic Performance of Secondary School Students in Physics - Emmanuel Edoja Achor; Jonah Joel Kyado; Esther E. Ejeh; Kingsley I. Eba (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: This study aimed to investigate the perceived influence of test anxiety on the academic performance of secondary school students in physics in Benue State, Nigeria. Methodology: The research utilized a descriptive survey design, with a target population of 15,060 students from government-approved secondary schools in the Obi Local Government Area of Benue State. A random sampling technique was employed to select 250 students from five secondary schools. The data collection instruments employed were the Mathematics Text Anxiety Questionnaire (MTAQ) and Mathematics Performance Text (MPT). The collected data were analyzed using measures such as means and standard deviation to address the research questions, while the analysis of variance was conducted to test the hypothesis at a significance level of 0.05. Findings: The findings indicated a significant difference in the influence of test anxiety levels exhibited by students on their average performance in physics within the secondary schools of the Obi Local Government Area in Benue State. Moreover, the results revealed a significant difference in the influence of test anxiety levels exhibited by male students on their average performance in physics in secondary schools. Significance: Similarly, a significant difference was observed in the influence of test anxiety levels exhibited by female students on their average performance in physics within secondary schools. Based on these findings, recommendations for school management are proposed.